2018
DOI: 10.4315/0362-028x.jfp-18-033
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Technology Effects on Training Outcomes of Restaurant Food Handlers

Abstract: Food safety training does not always result in behavior change, perhaps because of flaws inherent in traditional training designs. New technologies such as augmented reality headsets or head-mounted action cameras could transform the way food safety training is conducted in the food industry. Training conducted with wearable technology presents visual content in the first-person or actor's perspective, as opposed to the traditional third-person or observer perspective. This visual hands-on first-person perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…According to this comparative study, motivation intervention for hand washing was conducted through feedback for participants' performance, with monetary reinforcement (coffee shop gift card) and goal setting at the meeting time during the posttraining period (70). In the results, hand washing performance did not show an improvement from knowledge-based training, whereas it (17). Thus, the video recorded the hand washing process from the point of view of the demonstrator, who wore the camera on their head.…”
Section: Resultsmentioning
confidence: 87%
“…According to this comparative study, motivation intervention for hand washing was conducted through feedback for participants' performance, with monetary reinforcement (coffee shop gift card) and goal setting at the meeting time during the posttraining period (70). In the results, hand washing performance did not show an improvement from knowledge-based training, whereas it (17). Thus, the video recorded the hand washing process from the point of view of the demonstrator, who wore the camera on their head.…”
Section: Resultsmentioning
confidence: 87%
“…In Brazil, however, the training of food handlers is only mandatory for matters related to food safety, where the objective is to guarantee the hygienic and sanitary conditions of the prepared food [17]. National [21,[31][32][33][34][35] and international studies [36,37], pointed out the effectiveness of training related to good manufacturing practices for food handlers. In this sense, it could be suggested that the training on the careful preparation of food for celiacs can positively affect the professional practice of food handlers.…”
Section: Discussionmentioning
confidence: 99%
“…When processes are augmented and thereby clarified through the use of AR devices, trainees and learners are more motivated [ 45 ], resulting in reduced worker hours and costs [ 46 ]. As reported by Clark et al [ 47 ], the use of AR HMDs brings innovation and effectiveness to food safety training in the food industry. One such application was developed by Albayrak et al [ 48 ], who used AR HMDs to effectively train restaurant workers using gamification and personalization.…”
Section: Agri-food Applicationsmentioning
confidence: 98%